Dickkopf‐1 expression is down‐regulated during the colorectal adenoma–carcinoma sequence and correlates with reduced microvessel density and VEGF expression. Issue 2 (12th February 2015) - Liu, Zhiyong; Sun, Baocun; Qi, Lisha; Li, Yixian; Zhao, Xiulan; Zhang, Danfang; Zhang, Yanhui
<x xml:space="preserve">Abstract</x> Aims Dickkopf‐1 (Dkk1), an antagonist of the Wnt–β‐catenin signalling pathway, has been reported to play a role in cancer progression. However, little is known about the role of Dkk1 during the colorectal adenoma–carcinoma sequence. This study aimed to elucidate the role of Dkk1 in tumorigenesis and angiogenesis in colorectal cancer. Methods and results We examined Dkk1 expression immunohistochemically in 476 colorectal tissue samples, including 46 sets of matched specimens. Dkk1 expression was down‐regulated during the colorectal adenoma–carcinoma sequence, both among the 476 samples and in the 46 sets of matched specimens. Dkk1 expression was correlated with decreased microvessel density (P < 0.05) and VEGF expression. In‐vitro 3D coculture experiments showed that Dkk1 overexpression in HCT116 cells inhibited tube‐like structure formation and down‐regulated VEGF expression in human umbilical vein endothelial cells. Xenografts of Dkk1‐overexpressing colorectal cancer cells were smaller, and showed lower microvessel density and VEGF expression levels, than those of control cells. Conclusions This study is the first to show the roles of Dkk1 during the colorectal adenoma–carcinoma sequence, which may involve suppression of the tumorigenesis and angiogenesis of CRC. Dkk1 could therefore serve as a potential target for tumour therapy.